Ginsenoside Rb2 Alleviated Atherosclerosis by Inhibiting M1 Macrophages Polarization Induced by MicroRNA-216a - Wang, Shuting; Yang, Shujun; Chen, Yu; Chen, Yutong; Li, Rongxia; Han, Shuang; Kamili, Adalaiti; Wu, Yiyi; Zhang, Weili (Frontiers in Pharmacology, 2022)
Introduction: Atherosclerosis is a chronic disease characterized by the inﬂammatory process and lipid depositions. We previously reported that microRNA-216a (miR-216a) can accelerate the progression of atherosclerosis by promoting the polarization of M1 pro-inflammatory phenotype. Ginsenoside Rb2 (Rb2), the major pharmacologically active compound extracted from ginseng, has a high affinity with miR-216a. In this study, we aimed to investigate whether Rb2 can counteract the effect of miR-216a in macrophages to ameliorate atherosclerosis. Methods: The apolipoprotein E deficiency (ApoE-/-) mice model was chronically infected with miR-216a adenovirus via the tail vein and then intraperitoneally injected with Rb2. The plaque lesion area and stability of thoracic aorta were examined. The human myeloid leukemia mononuclear cells (THP-1) or human peripheral blood mononuclear cells (PBMCs) were cultured in vitro, transfected with miR-216a mimics, and treated with Rb2 to explore the mechanisms of Rb2 on the polarization of M1 macrophages, inflammatory process, and lipid accumulation. Results: In atherosclerotic ApoE-/- mice model, miR-216a greatly increased en face aortic lesion area of thoracic aorta, the lipid accumulation and M1 macrophages infiltration in plaques, whereas these effects of miR-216a on atherosclerosis burden were significantly alleviated by Rb2 treatment. In the THP-1 model in vitro, flow cytometry experiment showed that Rb2 treatment inhibited the miR-216a-mediated polarization of M1 macrophages characterized by the surface marker CD86 expression, but had no effects on M2 polarization characterized by the surface marker CD206 expression. Mechanistically, Rb2 suppressed the miR-216a-mediated inflammatory response through the Smad3/ nuclear factor kappa B inhibitor alpha (IκBα) pathway. Moreover, Rb2 reduced the lipid uptake and promoted the cholesterol efflux by counteracting effects of miR-216a in the THP-1-derived foam cells and in the PBMC-derived foam cells under the oxidized low-density lipoproteins. Conclusion: Our findings indicated that Rb2 might be a potential therapeutic molecule for atherosclerosis by attenuating the atherosclerosis plaque lesion, lipid accumulation, and M1 macrophages polarization by targeting the miR-216a. Given that accumulation of foam cells in the intima takes place chronically, the role of Rb2 in atherosclerosis progression needs further investigation.